The Influence of Auditor Expertise, Time Pressure, and Auditor Experience on Audit Quality with Ethics as a Mediating Variable - Mannan, Arifuddin; ., Sabir; H.S, Rahmawati; Bandang, Agus; ., Kahar; H.I., Irwan; ., Hasriyanti (Journal of Ecohumanism, 2025)
This study aims to determine the influence of auditor expertise, time pressure, and auditor experience on audit quality, mediated by auditor ethics. The population and sample in this study comprised 115 auditors from the Inspectorate of Regional Government in the districts and cities of South Sulawesi Province. Data collection was conducted through a questionnaire method, where structured statements were distributed referring to the research variables. The findings of this study indicate that auditor expertise, auditor experience, and auditor ethics positively affect audit quality, while time pressure has a negative effect on audit quality. Additionally, the findings reveal that auditor ethics mediates the relationship between auditor expertise, time pressure, and auditor experience on audit quality. These results contribute to the theoretical foundation of auditing, particularly in improving audit quality. Future research is expected to increase the sample size and expand its coverage to several provinces or even the entire country of Indonesia.